O ISS e a sua incidência na importação de serviços - Dantas, Leticia B. Tourinho (2010)
The objective of this work is to study the rules that deal with the impact of the tax services (ISSQN) in situations that characterize the import of services in order to verify its compatibility with positive legislation. The research has as its starting point the analysis of the constitutional text, seeking to build content, meaning and scope of prescriptive statements that impact directly on the legal regime of the ISS. In this plan, we focus the study of standards of competence of the ISS and what constitutes it and other infraconstitucional enunciations, through studying the role of supplementary law on the conformation of the legal system of the ISS. Traced the boundaries of both substance and form that define the institution of Tax Services at the constitutional level, the archetype of this constitutional duty is achieved, partly to investigate these prescriptive statements introduced in the legal system from the LC 116/03, analyzing the limits of positive law, each of the criteria of the rule of taxation possible from the ISS by building their semantic content, focusing on those that can trigger further discussions in relation to the tax in imports of services, namely the substantive test, the space and subjective criteria. We concluded that neither the constitutional legislator nor complement legislator, the determination of the substantive (conjugation of the verb with the complement), limited, both vehicles sheaths to address the possible materiality of the tax as the provision of services. On the space criterion, closely related to the principle of territoriality, we verify the possibility of adopting the principle of origin, as well as the destination on the taxation of services, being indispensable to the location of taxable activity the existence of evidence of connection to the Brazilian legal system, in order to legitimize the tax. Regarding the subjective criterion, especially on the topic of passive submission, we note that the legislature has the freedom to choose those which are responsible for compliance with the tax liability within the prescribed limits, may choose different person from the one who gets the economic benefit arising from activity of service provision, provided that there is another rule that permits restitution (reimbursement or retention). That done, we begin the analysis of rule of tax incidence of the incident ISS on the import of services covered by the same method in the previous steps, proving its compatibility with the Brazilian legal system